Bali's Local Government Paradiplomacy through Collaboration of Balinese Endek Fabric with Christian Dior - Fandy, Samantha Putri; Widya Nugraha, A.A. Bagus Surya; Wiranata, I Made Anom (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 4 (2025): JURNAL DIKSHI, 2025)
Balinese endek woven cloth is one of Indonesia’s cultural heritage products and national export commodity that is being promoted through paradiplomacy by the Indonesian Government through the Bali Provincial Government. By qualitative research methods, this study analyzes how the Government of Bali, as a part of the Indonesian Government carries out Indonesian cultural diplomacy through Balinese endek cloth in a collaborative project with Christian Dior. This study using data that is obtained through news analysis or statements from accountable parties, i.e. the Indonesian Ministry or Government of Bali, as well as literature studies on relevant topic. This research found that Indonesian cultural diplomacy through Balinese endek cloth with Christian Dior, succeeded in increasing awareness and economic demand for Balinese endek, making it profitable for the creative industry sector during the pandemic and the economic recovery period. The increasing people's awareness is also aligned with the long-term goal of Balinese endek diplomacy, which is carried out simultaneously through cultural diplomacy.